2002
DOI: 10.1152/ajpheart.00828.2001
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of heat shock-induced cardioprotection by treatment with the opiate receptor antagonist naloxone

Abstract: Attenuation of heat shock-induced cardioprotection by treatment with the opiate receptor antagonist naloxone. Am J Physiol Heart Circ Physiol 282: H2011-H2017, 2002. First published January 17, 2002 10.1152/ajpheart.00828.2001.-Whole body hyperthermia induces heat shock proteins (HSPs), which confer cardioprotection. Several opioid receptor subtypes are expressed in the heart and are linked to cardioprotection; however, no one has attempted to link the protection elicited by heat stress (HS) to opioids. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…We found that the myocardial infarct caused by ischaemia and reperfusion was significantly greater in diabetic than in nornist, attenuates both the cardioprotective effect and increased expression of HSPs [15].…”
Section: Discussionmentioning
confidence: 73%
“…We found that the myocardial infarct caused by ischaemia and reperfusion was significantly greater in diabetic than in nornist, attenuates both the cardioprotective effect and increased expression of HSPs [15].…”
Section: Discussionmentioning
confidence: 73%
“…Furthermore, opioids may protect against damage if administered during the window of opportunity after ischemia sets in but prior to reperfusion [Chang et al, 2005]. Blocking opioid receptors with naloxone (a general opioid antagonist) also attenuated the protective effect of heat stress preconditioning in a study [Patel et al, 2002], further supporting the role opioids may play in ischemia-reperfusion protection. Note that the different opioid receptor subtypes appear to have different functions in this regard.…”
Section: Mechanisms: Opioidsmentioning
confidence: 83%
“…18, 30, and 31). However, there is also evidence that its increased expression is not required for improved myocardial tolerance to I/R in young rats after one to three bouts of exercise (13,34) and that increased expression of HSP70 after heat shock does not necessarily result in cardioprotection (16,28,37). Whereas HSP70 could have played a major role in exercise-induced cardioprotection in the youngest group, this is unlikely to be the case in the older groups because the expression of the chaperone was only modestly elevated after exercise.…”
Section: Discussionmentioning
confidence: 99%